Rancang bangun aplikasi purchasing - Caesar Ratu Atika; Sharyanto Sharyanto; Raditya Galih Wendasmoro (Jurnal Manajamen Informatika Jayakarta, 2022)
The buying and selling activity is an activity that is absolutely vital for the success of a company because if the buying and selling activities run smoothly then the income that enters the company will be stable and so the company can easily develop. PT. Multitrend Indonesia (Kanmo Retail Group) is a company engaged in retail. In the purchasing process that is running at PT. Multitrend Indonesia has many obstacles, for example, when processing orders, the request form for goods is often lost, which slows down the process of purchasing goods. In addition, purchasing goods from suppliers also often experiences delays because all purchase orders made must wait for approval by the director directly. the method used in making this system is the Unifield Modeling Language (UML) method and the programming language used is Hypertext Preprocessor(PHP) while Mysql as the database